Políticas de direita e branquidade: a presença ausente da raça nas reformas educacionais - Michael Apple W. (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
In this article the author defends the need to incorporate discussion on race in educational analysis. He shows that racial dynamics are extremely complex and relatively autonomous and that they are connected to other social dynamics such as class, gender and colonial realities, operating in a subtle and powerful way in the educational field. The author also discusses the effects of educational policies pointing to the fact that current educational reforms are attempting to convince us that they are the only acceptable ones and that such policies are based on neoliberal ideological propositions. Behind these attempts to convince us of what is acceptable in ideological and political terms, we encounter the hidden presence of race.